Annual leave pursuant to the provisions of the labour code - MAJCHRZAK, KATARZYNA (Prawo Kanoniczne, 2016)
The article discusses the issues associated with annual leave pursuant the provisions of the labour law. The main purpose of an annual leave is to provide an employee with the opportunity to rest so she or he can fully regenerate physical and mental strength and efficiently perform the prescribed duties. The annual leave mechanism features primarily a protective function. An employee is entitled to annual leave every year, the leave is fully paid and it cannot be waived. Annual leave is a privilege, which, given its purpose, should be provided in its natural form, in other words the employee should use the time off from work he or she is entitled to. However, in situations where the employee cannot utilise his or her annual leave in nature, he or she is entitled to cash equivalent. Every employee is entitled to annual leave, that is why it should utilised in the calendar year in which this entitlement arises. Without doubt the use of this entitlement affects the organisation of the workplace and may often interfere with the normal course of work, and for that reason the legislator has introduced annual leave planning. Juvenile employees enjoy annual leave entitlement which is more favourable than in case of adult employees. Reasons for such solution include their age and young organism that requires more time for rejuvenation as well as the opportunity to gradually adapt to their professional duties.